Carving devotion in the Jain caves at Ellora - Owen, Lisa N. (Brill's Indological library, 2012)
Drawing on art historical, epigraphical, and textual evidence, this book is the first full-scale reconstruction of medieval Jain activities at Ellora. It not only highlights the understudied Jain caves, but examines them in concert with Ellora's Hindu and Buddhist monuments.